Climate resilient strategies for rice production in Jharkhand towards fulfilling food security - Ahmad, Ekhlaque; Singh, Ashok Kumar; Prasad, Krishna; Barnwal, M.K.; Kumar, Binay; Rani, Varsha; Singh, O.N. (Indian Council of Agricultural Research, 2023)
Rice is a major staple food crop of Jharkhand, mainly cultivated in Kharif season, because rainfed crops fulfil only 50% of food-grain requirements of the state. Women of the farming community in the state play a pivotal role in farm operation and rice cultivation— about 75%. Migration is a major bottleneck of resource-poor rural people for livelihood. Therefore, an integrated system approach is envisaged for selfsufficiency in rice production. Jharkhand is a state with a high population of tribal farmers (28%) who have a traditional farming system and mostly fall in category of marginal farmers. Cultivable land in the state is dominated by acidic soil, with only 16% assured irrigation facilities during kharif season. However, forest coverage is around 29.6% with an average annual rainfall of 1400 mm. Resource-poor farmers practice traditional mono-cropping with low inputs. The average land holding per family is less than one hectare. People cultivate rice mostly in the uplands, and the medium and lowland in a scattered manner, which brings down the average productivity. Birsa Agricultural University is working to uplift the tribal-dominated population of the state with rice crop improvement and has released many varieties suitable for different ecology of rice cultivation—like Birsa Vikas Dhan-111, Birsa Vikas Dhan 203, Birsa Vikas Sugandha-1—in recent years while collaborating with national and international institutes for releasing and promoting varieties like IR-64 (drt-1), Sahbhagidhan, etc. Quality seed acts as a catalyst in agricultural production, and is the most vital and critical input playing a significant role for the efficiency of the other inputs. A seed-rolling plan for producing quality HYV rice seeds of 20,507 tons would help timely availability to the farmers to make the state self-sufficient. In the recent past, several varieties have been released which are water efficient, nutrient efficient and nutrient dense to fulfil the dream of systemic approach for seed production. Direct seeding of rice is also advocated for maintaining the climate resilience in Jharkhand. This technology is affordable and time saving in crop establishment, advances the crop planting by 15–20 days, saves fuel and labor, reduces production cost, reduces irrigation water needs, reduces weed populations of particular species, reduces carbon emissions, increases crop yield by 5–10%, increases farm income and reduces emission of greenhouse gases.